Improving Early Childhood Language Development through “Kiki Miu-Miu” YouTube Videos - Jasiah; Umul Khasanah; Wina Asry; Nur Latifah; Zulham (Journal of Childhood Development, 2023)
This article aims to examine the importance of language development in early childhood, specifically focusing on the YouTube video "Kiki Miu-Miu" as a tool for learning and entertainment. The study utilized a qualitative methodology, involving two groups of families: 5 families with children aged 2-4 years, and 5 families with children aged 5-6 years. The findings revealed that videos containing appropriate educational content can contribute to improving children's language skills. However, the utilization of YouTube videos also brings potential challenges, such as fostering passive viewing habits, exposing children to inappropriate content, and limiting opportunities for social interaction. The involvement of parents or caregivers is therefore crucial in monitoring and limiting children's viewing time, as well as ensuring that the content chosen is appropriate for their age and stage of development.